Decadal‐scale sensitivity of Northeast Greenland ice flow to errors in surface mass balance using ISSM. Issue 2 (20th May 2013) - Schlegel, N-J.; Larour, E.; Seroussi, H.; Morlighem, M.; Box, J. E.
Abstract : [1] The behavior of the Greenland Ice Sheet, which is considered a major contributor to sea level changes, is best understood on century and longer time scales. However, on decadal time scales, its response is less predictable due to the difficulty of modeling surface climate, as well as incomplete understanding of the dynamic processes responsible for ice flow. Therefore, it is imperative to understand how modeling advancements, such as increased spatial resolution or more comprehensive ice flow equations, might improve projections of ice sheet response to climatic trends. Here we examine how a finely resolved climate forcing influences a high‐resolution ice stream model that considers longitudinal stresses. We simulate ice flow using a two‐dimensional Shelfy‐Stream Approximation implemented within the Ice Sheet System Model (ISSM) and use uncertainty quantification tools embedded within the model to calculate the sensitivity of ice flow within the Northeast Greenland Ice Stream to errors in surface mass balance (SMB) forcing. Our results suggest that the model tends to smooth ice velocities even when forced with extreme errors in SMB. Indeed, errors propagate linearly through the model, resulting in discharge uncertainty of 16% or 1.9 Gt/yr. We find that mass flux is most sensitive to local errors but is also affected by errors hundreds of kilometers away; thus, an accurate SMB map of the entire basin is critical for realistic simulation. Furthermore, sensitivity analyses indicate that SMB forcing needs to be provided at a resolution of at least 40 km. Key Points: The model smooths ice velocities, even in response to extreme errors in forcing. Mass flux is sensitive to local errors, but is affected by errors 200 km away. Ice flow simulation requires a surface forcing resolution of at least 40 km.